La exposición como estrategia metodológica para mejorar la expresión oral en el bloque curricular N°4 Juegos de palabras del área de lengua y literatura en los estudiantes del cuarto grado del subnivel de básica media de la escuela de educación básica municipal Borja, del barrio San Francisco de Borja del cantón y provincia de Loja. Periodo lectivo 2014-2015 - Jimenes Acaro, Verónica Patricia (2016)
This research work done regarding exposure as a methodological strategy to improve oral expression in Block Curricular No. 4 "Word Games" Area Language Arts students in the fourth grade sublevel of primary and secondary school Municipal Borja basic education, neighborhood san Francisco de Borja canton and province of Loja. 2014-2015 academic year; therefore the overall objective of using the exhibition as a methodological strategy to improve oral expression in curricular No. 4 "Wordplay" the Department of Language and Literature in the fourth grade students of the School of Basic Education Municipal proposed Borja; the development of it was pre-experimental and transversal character that allowed evaluate students before, during and after the workshops applied; deductive, scientific, statistical, analytical, synthetic methods provided in the process and analysis of information obtained from the survey technique applied to thirteen students through the instrument of the questionnaire was used; and, thereof directed in the guide questions to the teacher; that served to justify the issue investigated; as a result of the investigation it is concluded that the application of exposure contributes in reducing deficiencies speaking students presented in accordance with the development of their language skills; in this context it is recommended to teachers and authorities, applying exposure as a methodological strategy to reduce them and improve their education.